Assessing and Addressing Cardiovascular Health in LGBTQ Adults: A Scientific Statement From the American Heart Association. Issue 19 (10th November 2020) - Caceres, Billy A.; Streed, Carl G.; Corliss, Heather L.; Lloyd-Jones, Donald M.; Matthews, Phoenix A.; Mukherjee, Monica; Poteat, Tonia; Rosendale, Nicole; Ross, Leanna M.
Abstract : There is mounting evidence that lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ) adults experience disparities across several cardiovascular risk factors compared with their cisgender heterosexual peers. These disparities are posited to be driven primarily by exposure to psychosocial stressors across the life span. This American Heart Association scientific statement reviews the extant literature on the cardiovascular health of LGBTQ adults. Informed by the minority stress and social ecological models, the objectives of this statement were (1) to present a conceptual model to elucidate potential mechanisms underlying cardiovascular health disparities in LGBTQ adults, (2) to identify research gaps, and (3) to provide suggestions for improving cardiovascular research and care of LGBTQ people. Despite the identified methodological limitations, there is evidence that LGBTQ adults (particularly lesbian, bisexual, and transgender women) experience disparities across several cardiovascular health metrics. These disparities vary by race, sex, sexual orientation, and gender identity. Future research in this area should incorporate longitudinal designs, elucidate physiological mechanisms, assess social and clinical determinants of cardiovascular health, and identify potential targets for behavioral interventions. There is a need to develop and test interventions that address multilevel stressors that affect the cardiovascular health of LGBTQ adults. Content on LGBTQ health should be integrated into health professions curricula and continuing education for practicing clinicians. Advancing the cardiovascular health of LGBTQ adults requires a multifaceted approach that includes stakeholders from multiple sectors to integrate best practices into health promotion and cardiovascular care of this population.